The display flights of Shelduck - Hori, John (Wildfowl, 1965)
Display flights have been described for various species of Anatidae, but the flights of Shelduck Tadorna tadorna have not been noted. Aerial pairing displays are most frequent in May, with the greatest volume in the first half, although I have also seen these in other months, particularly February and March. As with dabbling ducks, displays centre on a single female and involve varying numbers of males; up to eight have been observed in North Kent, but larger numbers may occur. Flights usually originate when an unpaired female rises from a fresh water fleet or pool where she has been 'attended' by a number of unpaired males... Pairing display flights have to be distinguished from sexual pursuits of mated females which also occur at this period. In the latter unmated males, predominantly sub-adults, attempt to break up established pair bonds; such attempts often attract further unmated males and violent aerial pursuits can result. However, these never contain the 'gliding phase' and vocalization described above, whilst the aggressive nature is quite distinct from the 'darting' phase of the display. Further, the mated male invariably defends the pair bond, clashing with other males in mid-air and driving them off.